(untitled) (International Journal of Engineering and Computer Science, 2015)
: A unified trust management scheme that enhances the security in MANETs using uncertain reasoning is proposed. In the proposed scheme, the trust model has two components: trust from direct observation and trust from indirect observation. With direct observation from an observer node, the trust value is derived using Bayesian inference, which is a type of uncertain reasoning when the full probability model can be defined. On the other hand, with indirect observation from neighbor nodes of the observer node, the trust value is derived using the Dempster-Shafer theory, which is another type of uncertain reasoning when the proposition of interest can be derived by an indirect method. Performance of a routing protocol including this trust management scheme is evaluated under attack. Trust management considers the capability of the node along with its behavior while calculating the trust. Hence the performance of the routing protocol is improved when both behavior and capability is considered for trust evaluation.